Butir-butir mutiara Mahabharata - Danta, I Wayan (Departemen Pendidikan dan Kebudayaan, Proyek Penerbitan Buku Sastra Indonesia dan Daerah, 1981)
Collection of Balinese stories in romanized text, with references to the Mahabarata.